Real-world effectiveness of long acting aripiprazole: Treatment persistence and its correlates in the Italian clinical practice. (February 2019) - Fagiolini, A.; Aguglia, E.; Ballerini, A.; Callista, G.; Carpiniello, B.; Clerici, M.; Corrivetti, G.; De Fazio, P.; De Filippis, S.; De Giorgi, S.; Favaretto, G.; Ferri, E.; et al.
Highlights: Treatment persistence refers to the act of continuing a medication over time and may be an indirect measure of efficacy and tolerability. A relatively high number ( n  = 225, 86%) were persistent to A-LAI for at least 6 months. A statistically significant difference between persistent and non-persistent subjects was observed for baseline education, occupation, CGI-S, LDPS disorganization score, psychotic spectrum paranoid and schizoid score. All subjects with baseline CGI-S of 1 or 2, 95% of subjects with CGI-S of 3, 86% with CGI-S of 4, 82% of subjects with CGI-S of 5, 73% of subjects with CGI of 6 and 90% of subjects with CGI of 7 were persistent. A-LAI treatment continuation rate was higher in patients with: 1) baseline CGI score ≤ 4; 2) schizophrenia dimension (LDPS) mania score ≤ 5; 3) psychotic spectrum schizoid score ≤ 11. Abstract: Objectives: To identify the variables that are associated with persistence to Aripiprazole-Long Acting (A-LAI), in adult patients with schizophrenia. Methods: Observational, retrospective, non-interventional study involving 261 patients with schizophrenia. Results: Eighty-six percent of study subjects were persistent for at least 6 months. All subjects with baseline CGI-S of 1 or 2, 95% of subjects with CGI-S of 3, 86% with CGI-S of 4, 82% of subjects with CGI-S of 5, 73% of subjects with CGI of 6 and 90% of subjects with CGI of 7 were persistent. A-LAI treatment continuation rate was higher in patients with: 1) baseline CGI score ≤ 4; 2) schizophrenia dimension (LDPS) mania score ≤ 5; 3) psychotic spectrum schizoid score ≤ 11. Conclusions: A relatively high number of patients ( n  = 225, 86%) were persistent to A-LAI for at least 6 months. Not surprisingly, very severe patients were more unlikely to be persistent. However, it is noteworthy that a large number of subjects with high CGI score at the time when A-LAI was started (82% of subjects with CGI-S of 5, 73% of subjects with CGI of 6 and 90% of subjects with CGI of 7) were persistent. Larger, controlled, prospective and longer studies are warranted.